Deciding Thrombolysis in AIS Based on Automated versus on WhatsApp Interpreted ASPECTS, a Reliability and Cost-Effectiveness Analysis in Developing System of Care - Mansour, Ossama Yassin; Ramadan, Ismail; Abdo, Ashraf; Hamdi, Mohamed; Eldeeb, Hany; Marouf, Hazem; Elsalamawy, Doaa; Elfatatry, Amr; Elnekidy, Abdelaziz; Reda, M. Ihab (Frontiers in Neurology, 2020)
BACKGROUND: Automated ASPECTS has the potential of reducing interobserver variability in the determination of early ischemic changes. We aimed to assess the performance of an automated ASPECTS versus ASPECTS interpreted for sent CT images on WhatsApp and to correlate to outcome. MATERIALS AND METHODS: Patients with anterior circulation stroke who had baseline NCCT and underwent successful IV-thrombolysis were included. NCCT-ASPECTS was assessed by 2 neuroradiologists, and discrepancies were resolved by agreement. 2 groups of patients were included; group 1 where treatment decided after automated ASPECTS interpretation that was provided by RAPID software while group 2 those who received IV-tPA after assessment of CT images sent on WhatsApp. RESULTS: A total of 122 patients were included; 36 in group 1 and 86 in group 2. In group 2 The interobserver agreement for NCCT ASPECTS was moderate (κ = 0.36) and for dichotomized data was (κ = 0.44). While IOA improved to (κ = 0.57) and (κ = 0.64) when same CT images interpreted on workstation.In group 1 Automated ASPECTS showed excellent agreement with agreement reads (κ = 0.80) with agreement reads for workstation images. There was significant (P < .001) increased odds of functional independence and less hemorrhagic complications with thrombolysed patients in group 1. CONCLUSIONS: automated ASPECTS provided by the RAPID@IschemaView ASPECTS performs equally well with the agreement read of expert neuroradiologists and this performance was severely degraded when WhatsApp captured CT images used for ASPECTS assessment. In our study automated ASPECTS might predicting outcome after IV thrombolysis .